Systemic Changes of Preschool Education in European Union and Post-Communist Countries - Juodaitytė, Audronė (Acta Paedagogica Vilnensia, 2001)
New social democratic models and anthropocentric ideas significant changes in European formal and informal structures of education, and enhanced new model of educating society. Its essence is in the contexts of a person's (a child and adult) continues learning (formal and informal). Being an inherent part of the educational system, a kindergarten becomes an integral institution for the modern children and parents education. This it's importance in the society as a social-educational institution emerges. New meanings of early childhood and new models of humanistic interactions (adults - children) are enhanced by the development of the democratic society. This makes conditions for parents become equal partners with teachers, and participate in the modern development of educational process in the kindergarten. Changes in the social-educational sphere are significant for the creation of a new image of the kindergarten in the society, making it attractive for the parents and community. Thus a flexible, modern, humanistic, based on democratic values social-educational system of adult education is being created in the kindergarten. Equality of rights and equivalence of parents • -teachers' partnership in the strategic expansion of the child development model enhances creation of not only its new model, but also a model of adult education. The latter becomes an important part of the kindergarten's image. These new social-educational initiatives of the kindergarten give it a proper role in the education of the society, involving parents in the initial education by developing their understanding of social and anthropocentric senses in the educational process. In European (Germany, Great Britain) kindergartens concrete models of adult education (first of all – parents) are being developed. They are adapted to the needs of parents’ communities. The new system of system of views of the participants of social-educational process could make the creation of the modern kindergarten possible by taking into consideration global changes for the open society.
Keywords: Socio-cultural changes; new thinking; systemic change; preschool education.